(untitled) (Revista Contexto & Educação, 2022)
This reflective study was constructed with the aim of problematizing teaching in the context of Brazilian education, dealing specifically with teachers who work in the regular classroom and who are concerned with qualifying their practices and who, at the same time, are seeking possibilities for achieving truly inclusive education. Therefore, we propose to reflect on the knowledge, actions and commitments of teachers who work in an inclusive perspective, bringing to light the importance of teacher training for the discussion. Based on studies by Tardif (2002), López (2016) and Arroyo (2013, 2014), our reflections are based on the concept of inclusive teacher, which is understood by us as the professional who assumes as protagonist of his teaching and learning processes of all its students. In this direction, we structure our reflections from a proposal of a training triad, which presupposes the relationship between knowledge, actions and commitments, interconnected, composing the permanent construction of the inclusive professional. It is argued that each element of the triad is interdependent on the others, just as they all depend on the ongoing training and experience of each teacher, these processes being individual and collective at the same time.